Prevention and control of vascular catheter-related infections: Evidence-based nursing interventions - Xiaoyan Ai; Sushuang Ma; Na Zhang; Pei Zhang; Tao Liang; Haibin Chen; Lijiao Wang; Yongmei Wang (The Journal of Vascular Access, 2026)
Objective: This study aimed to develop and implement an evidence-based nursing intervention program for vascular catheter-related infection prevention and control within a specialized nursing alliance network, guided by the Ottawa Model of Research Use. Methods: A quasi-experimental implementation study with historical controls was conducted from January 2023 to December 2024 in 12 departments of a specialized nursing alliance. Consecutive eligible adults with central venous catheters or PICCs were enrolled (control, n = 160; intervention, n = 164). Outcomes were analyzed using crude incidence densities, exact Poisson tests, and multilevel models adjusted for clustering and calendar period. Implementation included evidence translation, barrier assessment, bundle delivery, audit and feedback, and mixed-methods evaluation. Results: Observed CLABSI events were fewer in the intervention phase (4/4468 vs 10/4136 catheter-days; 0.90 vs 2.42/1000 catheter-days). The univariate exact Poisson comparison showed a non-confirmatory trend (IRR = 0.37, 95% CI: 0.08–1.28; p = 0.108), while the adjusted model suggested a lower rate (IRR = 0.41, 95% CI: 0.23–0.73; p = 0.002) but was interpreted cautiously due to sparse-event overfitting risk. In 118 paired nurses, knowledge increased from 68.6 ± 12.1 to 86.7 ± 8.7, and overall bundle adherence increased from 60.1% to 90.2% (both p < 0.001). The adherence-infection model was exploratory (per 10% adherence increase: IRR = 0.82, 95% CI: 0.73–0.93; p = 0.001). Conclusion: The program produced robust process improvements and a promising downward trend in catheter-related infections. Rare-event infection estimates should be interpreted as hypothesis-generating, whereas the process findings support multilevel implementation strategies for catheter-care quality.